Kemandirian Pangan pada Masa Pandemik Covid-19 melalui Penerapan Teknologi Hidroponik di Kelurahan Wundudopi Kecamatan Baruga Kota Kendari - Sitti Wirdhana Ahmad; Nur Arfa Yanti; Muhsin Muhsin; Wa Ode Nanang Trisna Dewi (Jurnal Pengabdian Pada Masyarakat, 2021)
FOOD INDEPENDENCE DURING COVID-19 PANDEMIC THROUGH THE APPLICATION OF HYDROPONIC TECHNOLOGY IN WUNDUDOPI VILLAGE OF BARUGA DISTRICT, KENDARI CITY. Food security is one of the keys in the country development which is nowadays also affected by the Corona Virus Disease 2019 (COVID-19). The appeal about distancing and stay at home demands the community be able to maintain food security starting from household. Various activities can be carried out during the appeal to keep distancing and stay at home during the COVID-19 pandemic, especially those who can support household food needs, one of which is hydroponic organic vegetable farming. This activity is aimed to provide information, knowledge as well as practice on hydroponics farming techniques to produce vegetable crop products in an effort to maintain the food security during the COVID-19 pandemic. Participants who took part in this service program were the community groups Dasawisma Bukit Permai II and V Wundudopi Village, Baruga District, Kendari City. Community empowerment through the transfer of hydroponic technology starting with socialization and training in hydroponic farming, then continues with an evaluation to find out the Wundudopi community's perceptions of hydroponic farming technology. After implementing the program, participants experienced increased knowledge and gained skills in farming using hydroponic technology.